Health Problems of the International Travellers Visiting Agra City - Mehto, Amit Kumar; Misra, Sunil Kumar; Chaudhary, Shailendra Singh; Singh, Geetu (Indian Journal of Community Health, 2017)
Background: International travel to India is on the rise and the travellers comprise a diverse group of individuals in terms of their country of origin, preferences and risk taking behaviour. Different environment coupled with all other factors makes them more vulnerable to health problems. Aims & Objectives: To find out the health problems faced by the international travellers visiting Agra City, their perception and the factors associated with them. Material & Methods: Cross – sectional study design was used and International travellers in the age group 15 to 65 years were recruited from prominent tourist places and train stations of Agra, which was sometimes during their tour and just before their departure respectively. Data collection was carried out for a period of six months i.e. from November 2015 to April 2016.Results: Out of the total 422 study subjects, 208 (48.2%) faced one or more health problems. Primary purpose of visit (religious, educational, visiting friends and relatives) and the duration of visit (more than two weeks) were found to be significantly associated with a negative health outcome. Diarrhoea (131, 63%), fever (87, 41.8%) and respiratory problems (50, 24%) were the most frequent problems and many of them had more than one problem. A majority of the participants perceived the risk of health problems to be high and more than half of the them reported having experienced culture shock (57.4%). Conclusions: There may be a need for a travel clinic at the destination. The benefit of such a new offer must be validated.